Aerial Photo Interpretation and its Application in Tropical forest Development - Versteegh, P. J. D. (Indian Forester, 1967)
Besides a general discussion of aerial photo interpretation some aspects of the use of aerial photographs in tropical forestry are rendered in this paper. Aerial photo interpretation, though already practised in the earlier stages of aerial aurvey came of age in tbe Second World War. Civil use of aerial photographs in the various disciplines rapidly developed thereafter. There is a basic difference in military and civil photo interpretation. The military carry out photo interpretation to obtain approximate information of enemy held areas of which little or no terrestrial data can be made available; civil use of aerial photographs compliments and reduces field-work rather than taking its place. In tropical forestry the use of aerial photographs became a necessity with the introduction of the many forest development schemes for hitherto unmanaged virgin forests in developing countries all over the world. Forest development is aimed at sustained high productivity and optimal conservancy of the forests. Forest industries, that can be established on the basis of the existing forest resources may provide some of the means to achieve these targets. In a forest inventory to evaluate the existing forest resources the aerial photograph has its greatest use. In a later stage the use of aerial photographs may be of equal importance to the forest management as it may facilitate compreshensive consideration for planning and decision making.